Pengaruh Produk Domestik Bruto, Ekspor Dan Kurs Terhadap Cadangan Devisa Di Indonesia - Fuji Astuty (Universitas Hamzanwadi, 2020)
This study aims to analyze the effect of gross domestic product, exports and exchange rate on foreign exchange reserves in Indonesia. This research is in the form of quantitative based on quantitative data and is associative to see the relationship between variables or more. The data used is time series data from 2001 to 2018 using Eviews 9.0. And sourced from Bank Indonesia, the Central Bureau of statistics and the Federal Reserve Bank of St. Louis. This research uses data analysis technique is multiple linear analysis. The results showed that the variables of gross domestic product, exports and exchange rates have a positive and significant effect on Indonesia’s foreign exchange reserve. The R-square value in this study is 95.36, indicating that 95,36% of the variation in foreign exchange reserves can be explained by the gross domestic product, exchange rates and exports, while the remaining 4.64% is explained by other variables outside of this research model